STRATEGI KOMUNIKASI KANTOR PERWAKILAN BURSA EFEK INDONESIA (KP BEI) JATENG II DALAM LITERASI PASAR MODAL - Atik Nurfatmawati; Dedi Rismanto; Nadhiroh Nadhiroh (Bajang Institute, 2023)
The Central Java II Indonesia Stock Exchange Representative Office (KP BEI) has 26 Investment Galleries located in the former Surakarta Residency area. The purpose of this research is to find out the communication strategy used by KP BEI Central Java II in providing education about the capital market. The socialization process cannot be separated from the role of the Financial Services Authority (OJK) and Securities. The purpose of this study was to determine the communicator's strategy, message strategy and media use strategy in implementing capital market literacy education. The study used a qualitative descriptive approach with data sources obtained through observation, interviews and documentation. The results showed that the communicator's strategy of KP BEI Central Java II was to collaborate with educational institutions to form a capital market study group to establish an investment gallery, while also involving micro, small and medium-sized businesses that have an influence on the community. Determination of the audience strategy consists of the general public, educational institutions such as schools and colleges and business actors. Message strategy through seminars, webinars, training, talk shows, advertisements. In the communication process there are several factors that must be considered, namely the communicator as the sender of the message, the communicator as the recipient of the message, and the means of communication. After communication there is a response in the form of a response from the recipient of the message to the sender of the message. The general message is to recognize the importance of learning about stocks and saving stocks. Strategies for using media through electronic, online and social media. For example, talk shows on radio, podcasts, live Instagram and Facebook, hybrid webinars linked to YouTube.